2011
DOI: 10.1093/toxsci/kfr153
|View full text |Cite
|
Sign up to set email alerts
|

Methyleugenol Genotoxicity in the Fischer 344 Rat Using the Comet Assay and Pathway-Focused Gene Expression Profiling

Abstract: Methyleugenol (MEG), a constituent of human food, induces malignant tumors in multiple tissues of rats and mice. Although MEG forms DNA adducts and induces unscheduled DNA synthesis in rat liver, it is negative in many in vitro genetic toxicity assays. In the present study, we evaluated MEG-induced DNA damage in the rat using (1) the alkaline Comet assay, (2) the oxidative Comet assay, and (3) expression profiling of genes associated with DNA damage pathways. Male F344 rats received single oral doses of 400 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…Several alkenylbenzenes including safrole [Lord and Ashworth, 2012], estragole [Jones and Go, 2010] and methyleugenol [Williams et al, 2013] form DNA adducts. In addition, safrole and methyleugenol were found to induce oxidative DNA damage in rat liver [Liu et al, 1999;Ding et al, 2011]. Based on these findings, we hypothesize that multiple genotoxic mechanisms, i.e.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Several alkenylbenzenes including safrole [Lord and Ashworth, 2012], estragole [Jones and Go, 2010] and methyleugenol [Williams et al, 2013] form DNA adducts. In addition, safrole and methyleugenol were found to induce oxidative DNA damage in rat liver [Liu et al, 1999;Ding et al, 2011]. Based on these findings, we hypothesize that multiple genotoxic mechanisms, i.e.…”
Section: Introductionmentioning
confidence: 82%
“…The different genotoxicity results from our studies of structurally similar compounds may be due to the different experimental designs: the methyleugenol study was an acute study (rats were sacrificed 1, 3, 6, 8, and 24 hr after single dose [Ding et al, ] while the present study is a sub‐acute study (rats were dosed at 0, 24, and 45 hr and terminated at 48 hr after the first treatment). A recent study demonstrated a time‐dependence of DNA adduct formation after i.p.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to induce chromosomal aberrations and endoreduplication in vitro (Maralhas et al, 2006). Other research suggests that methyleugenol may cause DNA damage in rat liver (Ding et al, 2011). However, it is unclear if CLO or one of its components could cause hepatotoxicity in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…After dissociating RAW 264.7 cells into single cell suspensions, global cell viabilities were determined using Trypan Blue exclusion tests. For the alkaline comet assay, 26 50 μ l of single-cell suspensions in PBS, derived from each treatment condition were mixed with 450 μ l 0.8% (diluted in PBS) low melting-point (LMP) agarose at 37 °C, and 100 μ l of this suspension was applied to microscope slides (Fisher Scientific, St. Louis, MO,) previously thin-coated with 1% agarose. After solidification of the LMP agarose/embedded cell mixture at 4 °C, the slides were placed in freshly prepared lysis buffer (2.5 M NaCl, 0.1 M ethylenediaminetetraacetic acid (EDTA), 10 mM Tris, 10% dimethyl sulfoxide (DMSO) and 1% Triton X-100, pH 10.0) at 4 °C in the dark for 3 h. The slides then were washed once in neutralization buffer (0.4 M Tris, pH 7.5) in the dark for 5 min at 4 °C and then transferred into chilled alkaline unwinding/electrophoresis solution (~300 mM NaOH, 1 mM EDTA, pH > 13) in the dark for 30 min to unwind DNA.…”
Section: Methodsmentioning
confidence: 99%